Sosialisasi Pencegahan Perundungan Di Lingkungan Sekolah SDN 1 Songak - Nurmaulia Khotmi; Muhammad Atha Iqbal; Hartini Hartini (FUNDAMENTUM : Jurnal Pengabdian Multidisiplin, 2024)
Bullying is any physical or psychological violence that is perpetrated repeatedly due to unequal power relations. Repeated frequency of bullying is at least more than once. The purpose of this socialization is to provide information to increase knowledge in all sectors involved in the school environment so as to minimize the occurrence of bullying behavior. This activity was carried out as a face-to-face seminar. In this activity the material presented was "Bullying". The method used in this activity is the presentation of material about bullying, sharing experiences from participants, and questions and answers. Overall the activity went smoothly and the participants seemed enthusiastic in sharing experiences that occurred in the community environment, besides that some participants seemed enthusiastic in asking questions and asking for advice in dealing with bullying behavior if it occurred in their respective living environments.